To arrest or to serve: school resource officers’ perceptions of zero-tolerance and the school-to-prison pipeline - Bush, Michael D. (Journal of ethnicity in criminal justice, 2024)
This study explores the link between zero-tolerance policies and the school-to-prison pipeline from the perspective of school resource officers. Zero-tolerance policies are disciplinary measures that exacerbate the school-to-prison pipeline by treating students like potential criminals and forcing them out of the educational system. Prior research has investigated the perspectives of students, teachers, principals, and the general public regarding school resource officers. However, there exists a research gap concerning the perceptions of school resource officers themselves regarding their role within the educational system. Semi-structured interviews were completed with a purposive sample (n = 25) of school resources officers from the Midwest. Some SROs emphasized the counselor/mentor role to provide emotional support to students, others were more inclined toward problem-solving or law enforcement and focused on rules enforcement. SROs express diverse views on the impact of zero-tolerance policies, with some acknowledging harm to students’ success and others displaying indifference or cynicism, often attributing responsibility to parents, teachers, or the students themselves.